CURBA VIZIBILITĂŢII BIBLIOTECII MUNICIPALE - SCOBIOALĂ, Genoveva (BIBLIOPOLIS, 2020)
The systematic issues of the journal of librarianship and information sciences BiblioPolis confirms the publication utility and evolution, devoted to the goal – promotion of activities and initiatives of the Municipal Library „BP Hasdeu” of library trends, offering spaces for librarians communication and specialists from culture, science and education field. This information source is useful for specialists with experience, and for future librarians through the cohabitation of theoretical approach and practical problems and is apreciated in other library editions.